Awareness of cardiovascular risk among persons with type 2 diabetes: a qualitative study - Lena Jutterström; Anna-Lena Stenlund; Julia Otten; Mikael Lilja; Karin Hellström Ängerud (International Journal of Qualitative Studies on Health & Well-Being)
Purpose To describe the process of becoming aware of and acting on personal cardiovascular (CVD) risk in type 2 diabetes (T2D). Method A purposive sample of 14 persons living with T2D participated in semi-structured, open-ended, in-dept interviews. The interviews were analysed with grounded theory. Result The analysis identified the core category “Balancing emotions, integrating knowledge and understanding to achieve risk awareness and act on it.” Five categories describe the movement from not being aware of the risk of cardiovascular disease (CVD) to becoming aware of this risk and taking action to reduce it. Persons with T2D need to transform their knowledge and experience of CVD risk and incorporate it in their individual situations. Emotional and existential experiences of CVD risk can lead to awareness about the severity of the condition and contribute to increased motivation for self-management. However, an overly high emotional response can be overwhelming and may result in insufficient self-management. Conclusion Persons with T2D seemed not to fully grasp their increased risk of CVD or recognize that self-management activities were aimed at reducing this risk. However, their awareness of CVD risk gradually increased as they came to understand the severity of T2D and became more emotionally and existentially engaged.